The Transformation of the Concept of Iddah in Indonesian Marriage Law: The Dialectic of Sharia Normativity and the Demand for Gender Equality - Moch. Choirul Musonifin; Halil Thahir (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The transformation of the concept of iddah in Indonesian marriage law has become a crucial issue in Islamic family law reform because it lies at the intersection of sharia normativity and the growing demands for gender equality in modern society. This study aims to analyze the dynamics of iddah regulations in the Indonesian marriage legal system and examine their relevance from the perspective of gender justice and maqāṣid al-syarī‘ah. The study uses a normative juridical approach with a literature study method through an analysis of Islamic legal sources, legislation, court decisions, and academic literature related to Islamic family law and gender issues. The results show that the concept of iddah in Indonesian regulations is still oriented towards classical fiqh constructions that place women as the primary subject of the waiting period obligation. However, scientific developments, changes in social structures, and increasing awareness of the principle of gender equality have encouraged the emergence of various reinterpretations of the purpose of iddah that emphasize aspects of offspring protection, legal certainty, and family welfare. This study concludes that the transformation of the concept of iddah needs to be directed towards a more contextual approach and one based on maqāṣid al-syarī‘ah so that it can maintain sharia values ​​while accommodating the principles of justice, equality, and protection of women’s rights in contemporary Indonesian marriage law.